Percutaneous Treatments for Valve Repair - Helwick, Caroline (MD Conference Express, 2007)
As new bioprostheses become available and implantation techniques are refined, an increasing proportion of patients with valvular disease are avoiding open surgery and undergoing percutaneous procedures. This article describes the advances that are making this possible.